Use of displacement method with STFT wavelet transformation for groundwater recharges prediction - Maharjan, Rajib (International Journal of Environment, 2015)
The main aspiration behind this study was to calculate groundwater recession parameter using recently developed method and to apply calculated parameter for calculation of groundwater recharge. The equation for the hydrograph recession curve can be utilized to predict groundwater recharge during each recession period. The steps involved during recession curve analysis include selection of analytical expression, derivation of recession characteristic and optimization of the parameters. Each segment shows the outflow process which creates short-term or seasonal influence. The variations recession rate causes problems for derivation of recession characteristics. To avoid variations in recession parameters Short Time Fourier Transformation (STFT) was used. While applying STFT in real runoff data recession segments were chosen by user. The selected segments were further used for calculation of groundwater recharge assuming a linear hydrological model. The runoff hydrograph represents consist of three components: surface flow, intermediate flow and base flow. The applications of wavelet transformation can differential those flow components into were short, intermediate and long wavelet periods. The displacement method was used to obtain further information from wavelet transformation and to verify its practical application in groundwater studies. DOI: http://dx.doi.org/10.3126/ije.v4i2.12632 International Journal of Environment Vol.4(2) 2015: 128-135